2007
DOI: 10.1111/j.1600-0854.2007.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

The BEACH Protein LvsB Is Localized on Lysosomes and Postlysosomes and Limits Their Fusion with Early Endosomes

Abstract: The Chediak-Higashi syndrome (CHS) is a genetic disorder caused by the loss of the BEACH protein Lyst. Impaired lysosomal function in CHS patients results in many physiological problems, including immunodeficiency, albinism and neurological problems. Dictyostelium LvsB is the ortholog of mammalian Lyst and is also important for lysosomal function. A knock-in approach was used to tag LvsB with green fluorescent protein (GFP) and express it from its single chromosomal locus. GFP-LvsB was observed on late lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 39 publications
2
47
1
1
Order By: Relevance
“…Initial characterization of beige mice suggested that Lyst functions to limit the rate of homotypic lysosome fusion (Oliver and Essner, 1975). This model for Lyst function was subsequently supported by many studies in humans (Stinchcombe et al, 2000), Dictyostelium Kypri et al, 2007), mice (Willingham et al, 1981;Hammel et al, 1987;Hammel et al, 2010), cats (Collier et al, 1985) and Drosophila (Rahman et al, 2012). An alternative model suggested that Lyst functions to control lysosomal fission instead of fusion (Burkhardt et al, 1993).…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Initial characterization of beige mice suggested that Lyst functions to limit the rate of homotypic lysosome fusion (Oliver and Essner, 1975). This model for Lyst function was subsequently supported by many studies in humans (Stinchcombe et al, 2000), Dictyostelium Kypri et al, 2007), mice (Willingham et al, 1981;Hammel et al, 1987;Hammel et al, 2010), cats (Collier et al, 1985) and Drosophila (Rahman et al, 2012). An alternative model suggested that Lyst functions to control lysosomal fission instead of fusion (Burkhardt et al, 1993).…”
Section: Introductionmentioning
confidence: 74%
“…Disruption of LvsB results in the accumulation of large acidic compartments, much like those observed in cells of CHS patients Wang et al, 2002). Characterization of the LvsB-null phenotype has provided definitive evidence of an important role for LvsB during progression of the endo-lysosomal pathway (Kypri et al, 2007). However, similar to the conundrum of deciphering Lyst function in other systems, studies in Dictyostelium have proposed both the fusion and fission models for LvsB function.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations